Molecular modeling of cationic porphyrin-anthraquinone hybrids as DNA topoisomerase IIβ inhibitors. (December 2017) - Arba, Muhammad; Ruslin,; Ihsan, Sunandar; Tri Wahyudi, Setyanto; Tjahjono, Daryono H.
Graphical abstract: mono-H2 PzP-AQ in the binding pocket of Topo Iiβ. Highlights: The interaction between cationic porphyrin-anthraquinone hybrids and DNA Topoisomerase IIβ is computationally investigated. MD simulation and binding free energy prediction were conducted. The predicted binding energies of tris-H2 PyP-AQ and tris-H2 PzP-AQ were much lower than that of the native ligand (EVP). Abstract: Human DNA Topoisomerase II has been regarded as a promising target in anticancer drug discovery. In the present study, we designed six porphyrin-anthraquinone hybrids bearing pyrazole or pyridine group as meso substituents and evaluated their potentials as DNA Topoisomerase IIβ inhibitor. First, we investigated the binding orientation of porphyrin hybrids into DNA topoisomerase IIβ employing AutoDock 4.2 and then performed 20-ns molecular dynamics simulations to see the dynamic stability of each porphyrin-Topo IIβ complex using Amber 14. We found that the binding of porphyrin hybrids occured through intercalation and groove binding mode in addition interaction with the amino acid residues constituting the active cavity of Topo IIβ. Each porphyrin-Topo IIβ complex was stabilized during 20-ns dynamics simulations. The MM-PBSA free energy calculation shows that the binding affinities of porphyrin hybrids were modified with the number of meso substituent. Interestingly, the affinity of all porphyrin hybrids to Topo IIβ was stronger than that of native ligand (EVP), indicating the potential of the designed porphyrin to be considered in experimental research.